If your adolescent has depression or bipolar disorder : an essential resource for parents - Evans, Dwight L. frey50; Andrews, Linda Wasmer (New York, N.Y. : Oxford University Press, 2005)
The Adolescent Mental Health Initiative series addresses some of the major mental health issues facing teenagers today--eating disorders, anxiety disorders, depression, and schizophrenia. Of the dozen or so books planned for the series, the first four, including the two presented here, focus on how parents and other adults, including teachers, coaches, guidance counselors, and even pediatricians, can help afflicted teens overcome the disrupting and often devastating challenges of these disorders. Each book is an authoritative guide that offers essential information such as how to go about getting a diagnosis, what the latest treatment options and prevention strategies are, how to help teens cope with mental illness at home and at school and, perhaps most importantly, what the warning signs and red flags are that parents and other adults should look out for in teenagers who may be at risk for these diseases. Combining the expertise of leading psychiatrists and psychologists with the experience of everyday people who have faced these disorders in their own children, the books are designed to help adults deal effectively with adolescent mental illness and to empower them to act immediately and wisely in getting teens the best available treatment possible. While coping with teenage moodiness can be difficult under any circumstances, it can be especially challenging if a teenager has a serious mood disorder. This concise, readable book is the definitive guide to understanding and getting effective help for adolescents with depression or bipolar disorder, designed for parents and other adults in contact with afflicted teens. It combines the most current scientific expertise available today--including the newest treatments and medications and the latest research findings on mood disorders--with no-nonsense, hands-on advice from parents who have faced these disorders in their own children. Among other topics, the book addresses the biochemical roots of adolescent mood disorders, the ongoing debate over psychiatric medications for young people, and practical strategies for helping a teen cope at home and at school. It concludes on a hopeful note, by reviewing the latest scientific evidence on methods of stopping mood disorders before they start or minimizing the risk of recurrence. A growing body of research now shows that early diagnosis and treatment of depression and bipolar disorder may reduce the severity of these diseases, both now and in the future. Including red flags to look out for and warnings on the dangers of doing nothing, this book will provide the information and tools parents need to help adolescents achieve the best possible outcome.
1. Introduction : more than ordinary moodiness -- 2. Understanding the disorders : what they are, what to expect -- Depression : characteristics, causes, and risk factors ; other conditions ; outlook for the future -- Bipolar disorder : characteristics, causes, and risk factors ; other conditions ; outlook for the future -- The dangers of doing nothing -- The meaning of mental illness -- 3. Getting the best treatment for your teen : medications, therapy, and more -- Your role in the treatment process -- Treatment of depression -- Treatment of bipolar disorder -- Handling a suicidal crisis -- Finding a mental health professional -- Making choices about hospitalization -- Finding other mental health services -- Navigating the mental health system -- 4. Living daily life : helping your teen at home and school -- Communicating with your teen -- Managing your home life -- Parenting with a partner -- Dealing with sibling issues -- Taking care of yourself -- Helping to prevent a recurrence of your teen's illness -- Working with the school -- Finding Support from other parents -- 5. Reducing risk : protection and prevention -- Developing optimism and resilience -- Reducing family risk factors -- Preventing suicide -- Looking at the big picture : prevention at the societal level -- 6. Conclusion : take action, take heart -- Glossary -- Resources -- Organizations -- Books -- Websites -- Resources for adolescents -- Resources for related disorders.
Keywords: Depression in adolescence; Manic-depressive illness in adolescence; Parenting; Depression chez l'adolescent; Psychose maniacodepressive chez l'adolescent; Role parental